Coordination chemistry of organotin (IV) complexes with bidentate and tridentate (NNNNN) donor ligands - Sim, Imelda Siew Ping (Universiti Malaysia Sarawak, UNIMAS, 2007)
Two ligands have been prepared by condensation reaction of 2-acetylpyridine with o-phenylenediamine and 2-acetylpyridine-o-phenylenediamine with acetophenone in 1:1 mole ratio. Organotin(IV) complexes have been synthesized where the ligands acted as bidentate N,N and tridentate N,N,N chelating agents, respectively. The characterization of the ligands (1-2) and their organotin(IV) complexes (3-11) has been made on the basis of elemental analyses, UV-visible and FTIR spectra studies. On the basis of analytical and spectral data, six-membered geometry and seven-membered geometry around organotin(IV) moiety have been proposed.